Pengaruh Kepribadian Guru Yang Empati Terhadap Pembelajaran Efektif - Asep Muljawan (STAI Asy-Syukriyyah, 2016)
Teaher is very determining of student success especially in teaching-learning process. Teacher is form of component that the must influential toward created learning, process nad result quality. Therefore, upgrading effort that is done to improve the quality of learning will not give significant contributor without supported by professional and qualified teacher. In teaching, teacher must have higt personality competence, because the personal is very getting rol in shoping student’ individual. Teachers’ personality empati is skill to do interaction or feed back relation between teachers- student and this is a principal requretment for learning effectife process. Teacher emphaty make interesting learning students attention motivating growing the conviction and inspiring the student to increase the learning.